Building trust among marine protected area managers and community members through scientific research: Insights from the Ningaloo Marine Park, Australia. (July 2018) - Cvitanovic, C.; van Putten, E.I.; Hobday, A.J.; Mackay, M.; Kelly, R.; McDonald, J.; Waples, K.; Barnes, P.
Abstract: The success of participatory marine governance arrangements is influenced by the levels of trust that exist between decision-makers and diverse stakeholder groups within the community. While the benefits of high levels of trust among these groups is well established, specific approaches to building trust remain largely unknown. The aim of this study is to understand the extent to which scientific research programs can enhance trust among marine protected area (MPA) managers and community members via an evaluation of the Ningaloo Research Program - a large-scale program of marine research in the Ningaloo Marine Park. Results from a survey of 125 local residents show that community members along the Ningaloo coast believe that scientific research is important for the management of the marine park, and strongly support government investment in scientific research in the region. Results also suggest that science undertaken through the Ningaloo Research Program has increased the extent to which community members trust local managers, which study participants believe has led to improved social and environmental outcomes in the region. Finally, additional opportunities are identified to maintain and further enhance trust between community members and MPA managers, via targeted communication and engagement programs that account for different personality 'types'. In particular, the establishment of citizen science programs might further build trust. These results suggest that scientific research could be used as a means to increase trust among decision-makers and community members when coupled with an effective communication and outreach program, thus enhancing the success of participatory marine governance arrangements. Highlights: Trust among MPA managers and resource users underpins successful governance. Trust can be built and maintained through scientific research programs. Effective communication and outreach program is essential for trust building. Communication and outreach efforts must be tailored to reach diverse audiences. Citizen science can enhance trust building among MPA managers and community.